Evaluasi Kemitraan Sekolah Dengan Dunia Usaha dan Dunia Industri dalam Mendukung Link and Match Pendidikan Vokasi - Imelda Imelda; Ambiyar Ambiyar; Hasan Maksum (Education Achievement: Journal of Science and Research, 2026)
The successful implementation of vocational education is closely related to the quality of collaboration between vocational schools and business and industry. Strengthening school–industry partnerships has become a strategic priority in supporting the Link and Match policy, which aims to align graduates' competencies with labor market demands. However, the effectiveness of these partnerships has rarely been evaluated comprehensively from the perspectives of program planning, implementation, and outcomes. This study aimed to evaluate the effectiveness of the partnership between SMK Negeri 1 Ranah Batahan and business and industry in supporting the implementation of Link and Match in vocational education using the Stake Countenance Evaluation Model. A descriptive evaluative approach was employed involving school leaders, vice principals, heads of study programs, productive teachers, the Special Job Placement Unit, and industrial partners selected through total sampling. Data were collected using questionnaires, interviews, observations, and document analysis, and were analyzed through descriptive statistics supported by qualitative interpretation. The findings indicate that the partnership program was generally implemented effectively, with the Antecedents, Transactions, and Outcomes components achieving average scores of 81.60%, 79.00%, and 77.80%, respectively, all categorized as good. The partnership contributed to curriculum alignment, teacher competency development, student workplace readiness, and stronger collaboration with industry, although improvements are still required in monitoring, industrial engagement, and the sustainability of collaborative programs. These findings suggest that the Stake Countenance Evaluation Model provides a comprehensive framework for assessing vocational school–industry partnerships and offers practical recommendations for strengthening Link and Match policies to improve the quality and relevance of vocational education.